Loneliness in the Hebrew Bible - Hildebrandt, Samuel; Kozlova, Ekaterina E. (Library of Hebrew bible/Old Testament studies, 2026)
"The issue of personal loneliness is an acute challenge in the 21st century, and any response faces the initial problems of definition and language in discussing such intensely private matters. The essays in this volume turn to ancient prose and poetry in the search for such articulation, as the Hebrew Bible offers a deep pool for reflections about terminology, the diversity within the lonely crowd, and the overlap between loneliness and theology"-- Provided by publisher